Spectroscopic Diagnostics of Spectral Lines Emission from Cu Plasma within the Visible Spectrum Range - Hayim Ch. Magid; Bushra Khamas Abbas; Dunia F. T. AL-Ani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
The creation and characterization of laser-induced plasma (LIP), a significant phenomenon in several applications, are influenced by the sample’s physical qualities as well as the laser’s parameters. In this research, we created Cu plasma in the atmosphere using an Nd: YAG laser operating at a wavelength of 532 nm with a laser irradiance energy range (400-800) mJ. The effect of the laser’s irradiance energy on the plasma characteristics was investigated using optical emission spectroscopy (OES). Using the two ratio and Stark broadening methods, we successfully measured the two most important plasma properties (electron temperature and electron density). The electron’s plasma temperature value ranged from 2.3 to 3 eV. The value of electron plasma density is in the range from 6.75×1017 to 15×1017 cm−3. Also, we found that other plasma parameters like plasma frequency (fp), particles in the Debye sphere (ND), and Debye length (?D) are affected by laser energy. Where plasma frequency ranged from 7.378 to 10.998×1012 Hz, the Debye sphere ranged from 7.294 to 7.022×103, and the range of Debye length from 1.372 to 1.038×10−5 cm.